THE RELATIONSHIP OF VACUUM CHILDBIRTH WITH THE INCIDENCE OF ASPHYXIA NEONATORUM - Fatsiwi Nunik Andari; Mika Ilma; Nurhayati Nurhayati; Panzilion Panzilion (Jurnal Vokasi Keperawatan (JVK), 2021)
Asphyxia neonatorum is a condition that needs attention because it is related to the quality of life so that at every delivery it is hoped that there will be no disabilities that can affect life in the future. The purpose of this study was to determine the relationship between the relationship of vacuum childbirth with the incidence of asphyxia neonatorum in RSUD Dr. M. Yunus Bengkulu. This research was a quantitative study with a cross sectional design. The total sample was 115 patients that who experienced asphyxia at birth by vacuum extraction. The results showed there was a significant correlation between vacuum childbirth with the incidence of asphyxia neonatorum in RSUD Dr. M. Yunus Bengkulu with p value <0.05.